Pengaruh Dukungan Sosial, Efikasi diri, Kesiapan Kerja terhadap Kecemasan Karir Pada Mahasiswa Tingkat Akhir - Arba Sunur; Nurbaiti; Sri Ramadhani (POLITEKNIK LP3I, 2026)
The purpose of this study was to examine the effect of social support, self-efficacy, and work readiness on career anxiety among final-year students. This study employed a quantitative approach using a survey method. The population consisted of 120 final-year students of the Management Study Program, Faculty of Economics and Business, State Islamic University of North Sumatra. A sample of 92 respondents was selected using a non-probability sampling technique based on the Slovin formula with a 5% margin of error. Data were collected through questionnaires that met validity and reliability requirements and were analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The results showed that social support had a negative and significant effect on career anxiety (Sig. = 0.027 < 0.05), and self-efficacy also had a negative and significant effect (Sig. < 0.001 < 0.05). In contrast, work readiness had no significant effect on career anxiety (Sig. = 0.554 > 0.05). Simultaneously, social support, self-efficacy, and work readiness significantly influenced career anxiety (Sig. < 0.001), with an R² value of 0.896. These findings indicate that social support and self-efficacy play important roles in reducing career anxiety among final-year students.